Fluorescence‐based endoscopic imaging of Thomsen–Friedenreich antigen to improve early detection of colorectal cancer. Issue 5 (31st July 2014) - Sakuma, Shinji; Yu, James Y. H.; Quang, Timothy; Hiwatari, Ken‐Ichiro; Kumagai, Hironori; Kao, Stephanie; Holt, Alex; Erskind, Jalysa; McClure, Richard; Siuta, Michael; Kitamura, Tokio; Tobita, Etsuo; et al.
<x xml:space="preserve">Abstract</x> Thomsen–Friedenreich (TF) antigen belongs to the mucin‐type tumor‐associated carbohydrate antigen. Notably, TF antigen is overexpressed in colorectal cancer (CRC) but is rarely expressed in normal colonic tissue. Increased TF antigen expression is associated with tumor invasion and metastasis. In this study, we sought to validate a novel nanobeacon for imaging TF‐associated CRC in a preclinical animal model. We developed and characterized the nanobeacon for use with fluorescence colonoscopy. In vivo imaging was performed on an orthotopic rat model of CRC. Both white light and fluorescence colonoscopy methods were utilized to establish the ratio‐imaging index for the probe. The nanobeacon exhibited specificity for TF‐associated cancer. Fluorescence colonoscopy using the probe can detect lesions at the stage which is not readily confirmed by conventional visualization methods. Further, the probe can report the dynamic change of TF expression as tumor regresses during chemotherapy. Data from this study suggests that fluorescence colonoscopy can improve early CRC detection. Supplemented by the established ratio‐imaging index, the probe can be used not only for early detection, but also for reporting tumor response during chemotherapy. Furthermore, since the data obtained through in vivo imaging confirmed that the probe was not absorbed by the colonic mucosa, no registered toxicity is associated with this nanobeacon. Taken together, these data demonstrate the potential of this novel probe for imaging TF antigen as a biomarker for the early detection and prediction of the progression of CRC at the molecular level.